(untitled) (Altre Modernità, 2015)
Maeterlinck’s drama is mostly a static drama, where there is very little action and this little is hesitant. This empirical aspect is connected to another (less evident) realization: in Maeterlinck’s theatre the future is never made pertinent, it is rather a representational impasse. Castles are ruins, but they don’t collapse; kings are old and decrepit, but alive nevertheless, while young people die instead. The lack of a future affects also the representation of space: the setting is always a closed, suffocating space, with locked doors and windows, and the characters seem to prefer their isolation to any outdoor experience. There is thus a compelling connection between the inability to conceive the future and the difficulty to come out of a recluse condition.